(untitled) (Research, Society and Development, 2024)
The dental anomaly Dens Invaginatus (DI), or Dens in dente, is an unusual condition that affects humans. Finding this anomaly means noticing some changes in dental anatomy that may possibly harm the patient and understanding that these cases are not treated with traditional endodontic methods. This study aimed to evaluate, in a retrospective and observational manner, the approach to DI cases to achieve success in endodontic treatment. Dental records, radiographs, and tomographies, when available, were analyzed. The data were collected at the EndoMais Private Clinic in Uberlândia, Minas Gerais. In total, 1,387 patients were included, of which only 5 teeth (2,77%) presented DI, predominantly in the upper lateral incisor (n=3) and in the upper central incisor (n=2). Most of the patients were female (n=5), and all were adolescents. Among the 5 cases, 4 were referred by other professionals, and only one received an initial intervention. The presence of DI was identified in 3 cases with spontaneous pain: 2 with localized and continuous pain and 1 with pulsatile pain. In the other 2 cases, there was no report of pain, and DI was discovered as a radiographic finding. Data analysis revealed three main challenges in the endodontic treatment of teeth with DI: coronal access, complete disinfection of the canals, and obturation due to complex anatomy. This study highlights the importance of accurate diagnosis and the use of advanced technologies for the success of DI treatment, serving as a basis for future investigations and improvements in clinical practice.